2007
DOI: 10.1016/j.ajic.2006.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions related to human avian influenza and their associations with anticipated psychological and behavioral responses at the onset of outbreak in the Hong Kong Chinese general population

Abstract: Panic and interruption of daily routines may occur in the event of a human avian influenza outbreak. Dissemination of accurate, timely information would reduce unnecessary distress and unwanted behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
98
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 8 publications
15
98
3
2
Order By: Relevance
“…The common use of face-masks might remind people of the stressful SARS experience, and anticipated panic with respect to avian flu was associated with one's SARS experience. 22 There is little reason for healthy people to use face-masks regularly at the time of this survey, but government guidance needs to be clear and authoritative.…”
Section: Discussionmentioning
confidence: 99%
“…The common use of face-masks might remind people of the stressful SARS experience, and anticipated panic with respect to avian flu was associated with one's SARS experience. 22 There is little reason for healthy people to use face-masks regularly at the time of this survey, but government guidance needs to be clear and authoritative.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in Hong Kong, almost all households have home-based telephone service. In addition, a large number of locally published studies on SARS or influenza vaccination [49][50][51] have utilized this research method and found credible estimations. This study managed to achieve a response rate of 69.9%, which is similar to many of the other local studies that have been published.…”
Section: Selection Biasmentioning
confidence: 97%
“…Avoidance behaviours and anxiety symptoms were experienced during the human avian influenza outbreaks and the SARS epidemic (7)(8)(9). During the 2009 H1N1 pandemic, anxiety was associated with high perceived susceptibility to infection and disease severity that influenced hygiene measures (5) or led to social distancing, rather than substantial changes in hygiene behaviour (10).…”
Section: Introductionmentioning
confidence: 99%